A STUDY OF PHRASES EXPRESSING THE RELATIONSHIP WITH PERSONAL THOUGHT AND PERCEPTION IN THE WORK “QUTADG ‘U BILIG” (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This work discusses the division of phrasemes into semantic groups in the work “Qutadgu bilig” written in the 11th century and the relationship of semantic groups to the individual. The use of phrasemes occurs in the ready state of speech. Such complex language units can be found in many places in the work “Qutadgu bilig” written in the ancient Turkic language. It can be observed that the phrasemes in the work are related to the thinking and perception of the individual. By introducing such phrasemes in the work, the author tried to skillfully reflect the image of the images in his speech. The relationship of such phrasemes to the current Uzbek literary language was also studied and analyzed comparatively. The use and expression of idioms in speech has made the text more attractive. Today, one can see that many idioms have come into use or that changes in the composition of idioms have occurred over time.